The Development of Management Model of Maharani Production Unit in Akademi Kesejahteraan Sosial Ibu Kartini Semarang to Improve Competency on Knowledge, Attitude and Skill - Daniati, Sofia; Sudana, I Made; Syamwil, Rodia (Journal of Vocational and Career Education, 2018)
The problem of managing the Maharani Production Unit is the weakness of the Production Unit management so that the utilization of Production Unit as a means of entrepreneurship training is not optimal. The objective of the study is to produce a valid and effective Production Unit management model. The method used in this study was Research and Development (R & D). The production unit management model was a college student-based  management model that did not only involve the college students on services but also on the management so that it can improve college students' competence in the aspects of knowledge, attitude, and skills. The implementation of this model was conducted by holding selection activities for production unit members and training activities before students manage production units. Participants who were interested in developing entrepreneurship skills through the production unit and have passed the selection then they followed the training activities that were conducted in five meetings with 20 participants. The result of management model of the Maharani production unit shows that the model that has been validated by the expert, it shows very valid with the average score of 62.75. In the small trial results also shows that the management model of Maharani production unit is effective, resulting from the paired sample t test with significance of 0.001 <0.05 this indicates that the model can improve students’ competence on the student’  knowledge and skills aspects. The results of the training can also be seen from the change of students’ attitude of in entrepreneurship which is scored from the confidence, responsible, leadership spirit, the way of communicating and have passion in seeking business opportunity. Besides, it can be a reference in conducting the production units activities, the developed model can provide experience and entrepreneurship skills for students.